Preferred intensity exercise for adolescents receiving treatment for depression: a pragmatic randomised controlled trial - Carter, Tim; Guo, Boliang; Turner, David; Morres, Ioannis; Khalil, Elizabeth; Brighton, Emily; Armstrong, Marie; Callaghan, Patrick (BioMed Central, 2015)
Background Exercise has been shown to be effective in treating depression, but trials testing the effect of exercise for depressed adolescents utilising mental health services are rare. The aim of this study was to determine the effectiveness of a preferred intensity exercise intervention on the depressive symptoms of adolescents with depression.